Civilizational Manifestations in the City of Astrabath in the Sixth Century AH (Journal of the College of Education for Women, 2023)
The current study is concerned with presenting a descriptive study of the history of the city of Astrabath in the sixth century AH. The problem that the research tried to answer is represented in the investigation of historical news, and the study of the most prominent cultural aspects which characterizing that city. The research also aims to reach the geographical location of that city, its name and its suburbs. The importance of the research lies in the knowledge of everything related to the role of the civilization of Astrabath, as well as tracing the entry of the Arabs to it, so that it became a cultural, economic and scientific center and its historical role in the sixth century AH. The research reminde us with the scientific role of the city of Astarbath in the fields of Qur’anic sciences and to the sciences of hadith, jurisprudence, the other sciences such as history, dialectics, medicine, prose, rhetoric, and systems. The study came out with several conclusions, the most important of which is that the city of Astrapaz was a military theater for political conflict, in addition to its great cultural role in all the popular sciences at the time, and it was a destination for scholars and jurists due to the popularity of its scientific and literary status.